The interface between metallurgy and mechanics in material performance - M. N. James; M. Newby (Fracture and Structural Integrity)
This paper considers an important topic, and one that is often poorly understood or misinterpreted, but which is a determining factor in many aspects of the service performance of metals (and other materials). Engineering components and structures must, of necessity, provide a bridge between the macroscopic, homogeneous and generally continuum aspects of applied load and displacement, and the microscopic, heterogeneous and often non-continuum reality of material structure and behaviour. This bridge can take the form of a genuine interface between material and environment, e.g. at a surface, or can be a virtual one where the differing philosophies of design have to be merged. The interface has particular importance in circumstances where environmental influences have a key role in determining performance characteristics (e.g. creep, environmentally-assisted cracking, or corrosion), where performance is dominated by fatigue or fracture, where welding is used to join components, or where tribology plays a role. The paper focuses on the problems associated with cracking and uses case study examples drawn from engineering practice to illustrate the role of metallurgical factors in mechanical performance of materials.